Implementasi Metode Project Based Learning melalui Pembelajaran Daring saat Pandemi Covid 19 - Didik Setiawan; Victor Novianto (UM Purwokerto Press, 2022)
Learning is a process of interaction between students and educators and learning resources in a learning environment. Ideal learning can be realized if it is supported by an ideal teacher. Therefore, teachers must be able to choose and use strategies or learning methods well. However, due to the COVID-19 pandemic, teachers must be able to adapt in choosing and using learning strategies or methods. One of the learning methods that can be used is the PjBL (project based learning) method. This study aims to describe how the implementation of the PjBL (project based learning) method and its effect on social studies learning outcomes during the covid 19 pandemic. This research method is a qualitative method. Data collection techniques with interviews and literature study. Interviews are used as a data collection technique if the researcher wants to know things from respondents who are more in-depth and the number of respondents is small or small. Literature study was carried out with a content approach. The data collected was then analyzed qualitatively with an inductive approach. The results showed that the PjBL (project based learning) method was widely used by teachers because this method was student-centered. The implementation of learning is focused on learning life skills/skills. The teacher gives projects to students to work on independently or in groups. The teacher monitors the progress of learning through WAG or google meet. This method is able to provide student activities that affect the improvement of learning outcomes.